Healthcare-acquired clusters of COVID-19 across multiple wards in a Scottish health board. (February 2022) - Dancer, S.J.; Cormack, K.; Loh, M.; Coulombe, C.; Thomas, L.; Pravinkumar, S.J.; Kasengele, K.; King, M.-F.; Keaney, J.
Summary: Background: Healthcare-acquired COVID-19 has been an additional burden on hospitals managing increasing numbers of patients with SARS-CoV-2. One acute hospital (W) among three in a Scottish healthboard experienced an unexpected surge of COVID-19 clusters. Aim: To investigate possible causes of COVID-19 clusters at Hospital W. Methods: Daily surveillance provided total numbers of patients and staff involved in clusters in three acute hospitals (H, M and W) and care homes across the healthboard. All clusters were investigated and documented, along with patient boarding, community infection rates and outdoor temperatures from October 2020 to March 2021. Selected SARS-CoV-2 strains were genotyped. Findings: There were 19 COVID-19 clusters on 14 wards at Hospital W during the six-month study period, lasting from two to 42 days (average, five days; median, 14 days) and involving an average of nine patients (range 1–24) and seven staff (range 0–17). COVID-19 clusters in Hospitals H and M reflected community infection rates. An outbreak management team implemented a control package including daily surveillance; ward closures; universal masking; screening; restricting staff and patient movement; enhanced cleaning; and improved ventilation. Forty clusters occurred across all three hospitals before a January window-opening policy, after which there were three during the remainder of the study. Conclusion: The winter surge of COVID-19 clusters was multi-factorial, but clearly exacerbated by moving trauma patients around the hospital. An extended infection prevention and control package including enhanced natural ventilation helped reduce COVID-19 clusters in acute hospitals.